2016
DOI: 10.1186/s41231-016-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of CFTR-mRNA transfection in human nasal epithelial cells

Abstract: Background: Cystic fibrosis (CF) is the most common life-threatening inherited disease in the Caucasian population. It is caused by genetic defects in the cystic fibrosis transmembrane conductance regulator gene (CFTR), a cAMP regulated chloride-bicarbonate channel mainly located in the apical membrane of polarized epithelial cells. CFTR is proposed to regulate other proteins, including the epithelial sodium channel (ENaC). Recently, we successfully restored chloride current in CFTR deficient human airway epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Chemical modification, using various techniques, has showed great improvements in the mRNA-based approach, especially in cancer therapy and vaccination for infectious diseases [148]. In vitro studies on differentiated human nasal epithelial primary cells revealed that the minimal dose of wt-CFTR-mRNA (0.6 µg/cm 2 ) delivered by lipofectamine 2000 unregulated the functional electrophysiology of the CFTR channel for over 72 h [149]. The efficacy of this approach was also demonstrated in vivo by Robinson et al (2018), where the CFTR mRNA restored the Clions efflux by 55% in CFTR knockout mice compared to healthy mice [150].…”
Section: Targeting Cftrmentioning
confidence: 99%
“…Chemical modification, using various techniques, has showed great improvements in the mRNA-based approach, especially in cancer therapy and vaccination for infectious diseases [148]. In vitro studies on differentiated human nasal epithelial primary cells revealed that the minimal dose of wt-CFTR-mRNA (0.6 µg/cm 2 ) delivered by lipofectamine 2000 unregulated the functional electrophysiology of the CFTR channel for over 72 h [149]. The efficacy of this approach was also demonstrated in vivo by Robinson et al (2018), where the CFTR mRNA restored the Clions efflux by 55% in CFTR knockout mice compared to healthy mice [150].…”
Section: Targeting Cftrmentioning
confidence: 99%
“…Generally, the average size diameter of chitosan-based complexes is determined by DLS. Complexes formed using a series of different chitosans range from few nanometers to less than a micron [ 81 , 93 , 101 , 113 ].…”
Section: Characterization Techniques Of the Biophysical Propertiesmentioning
confidence: 99%
“…Recently, a proof-of-concept mRNA-based functional restoration of impaired CFTR function have been demonstrated, not only in an immortalized human bronchial CF cell line, but also in primary human nasal epithelial (HNE) cells [ 113 , 249 ]. Transfection of the CFBE41o- cells with CFTR-mRNA restored cAMP induced CFTR currents similar to the values seen in control cells (16HBE14o-) and an almost two-fold increase in the cAMP-stimulated CFTR current after transfection using primary cultured HNE cells.…”
Section: Rare Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our group, we have been working with wtCFTR-mRNA to improve chloride secretion of epithelial cells constantly optimizing delivery methods [10][11][12]. The most promising delivery systems of nucleic acids to epithelial cells proved to be self-assembled polyelectrolyte chitosan (CS)-based nanocomplexes due to their low cytotoxicity and high transfection efficiency [12][13][14].…”
Section: Introductionmentioning
confidence: 99%